Epidemiologic Characteristics and Management of Sepsis Among Previously Healthy PatientsTake-Home Points - Rachel K. Hechtman, MD; Megan E. Heath, PhD; Jennifer K. Horowitz, MA; Elizabeth McLaughlin, MS, RN; Patricia J. Posa, RN, BSN, MSA, CCRN; John Blamoun, MD; Paul Bozyk, MD; Megan Cahill, DO, MBA, FACOEP; Rania Esteitie, MD, FCCP, ATSF; Kevin Furlong, DO; Namita Jayaprakash, MB, BcH BAO, MRCEM; Jessica Jones, PharmD; et al. (CHEST Critical Care)
Background: Most deaths resulting from sepsis occur among patients with advanced age, multiple morbidities, or frailty. It is unclear how many sepsis-related deaths truly are preventable. Previously healthy patients may provide insight into preventable sepsis mortality. Research Question: What are the baseline characteristics, management, and outcomes associated with previously healthy patients with sepsis? Study Design and Methods: This was a retrospective cohort of patients hospitalized for community-onset sepsis at 66 Michigan hospitals (November 2020-January 2024). We developed major and minor criteria to classify patients as previously healthy vs having significant comorbidities. We compared baseline characteristics, management, and outcomes of previously healthy patients vs patients with comorbid sepsis. Physicians reviewed charts of previously healthy patients with in-hospital death to evaluate baseline health status and rate preventability of death. Results: Of 29,688 patients hospitalized for sepsis, 2,963 patients (10.0%) were classified as previously healthy. Previously healthy patients had median age of 53 years, a median of 2 minor comorbidities, and lower in-hospital mortality (5.8% vs 12.7%; P < .01) vs comorbid patients. Delivery of guideline-recommended early sepsis management ranged from 56.8% to 80.9% across individual care practices. Several care practices were less common among previously healthy patients, including lactate measurement (67.5% vs 73.8%; P < .01) and timely antibiotic administration (58.0% vs 66.3%; P < .01), whereas some were more common, including ≥ 30 mL/kg fluid resuscitation (72.4% vs 55.3%; P < .01). Among 48 charts of previously healthy decedents reviewed, 77.1% of patients were deemed to have life expectancy > 5 years without sepsis. Most deaths were judged to be unpreventable because of severity of illness on presentation. Interpretation: We found that 1 in 10 patients with community-onset sepsis was healthy previously. Although gaps in in-hospital management were identified, deaths among previously healthy patients generally were deemed unpreventable with better in-hospital management because of patients seeking treatment too late in the course of sepsis. This study highlights system-level opportunities for better recognition and triage of sepsis before hospitalization.